Effects of COVID-19 Among People With Disabilities in Plumtree, Zimbabwe: A Mixed-Method Survey - Lindiwe Ndlovu; Nicholas Mudonhi; Nomathemba Sibanda; Wilfred Njabulo Nunu; Norman Manyeruke (SAGE Publishing, 2024)
Introduction: Persons with disabilities are the most affected by rising pandemics worldwide. COVID-19 has affected people with disabilities in many areas of their lives; however, its impact has been overlooked. This study aimed to assess the effects of COVID-19 on people with disabilities in Plumtree, Zimbabwe, to develop a disability-inclusive approach in response to COVID-19. Methods: A concurrent mixed-methods approach was used to collect qualitative and quantitative data from 7 key informants and ninety-two participants with disabilities, from January to May 2023. Quantitative data were analysed using STATA software version 12 and Microsoft Excel. Multiple Logistic Regression, Chi-square test, and paired-sample test were used to test for associations among COVID-19 cases, source of income, key challenges, and demographic characteristics. Qualitative data were analysed and presented in the form of themes. Results: We recruited more females (56.5%) than males with disabilities, and more than half were unemployed (56.5%). In contrast, only 3.3% of the respondents were formally employed. The results also indicated a significant relationship between age and COVID-19 positivity ( P = .025). The results also indicated that efforts were being made by government and non-governmental departments to assist people with disabilities during the pandemic through finance, food, awareness campaigns, and social support. Conclusion: Restriction measures put in place disturbed the livelihood of people with disabilities in Plumtree. Therefore, entrepreneurship programmes targeting vulnerable groups, including people with disabilities, should be introduced to ensure that their sources of income are sustained despite emergencies or pandemics.